DETERMINATION OF IMPLICIT OIL-AND-GAS-BEARING SAND INTERVALS BY STATISTICAL-CORRELATION INTERPRETATION OF GWS DATA - Igor A. Melnik (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Melnik I.A. Determination of implicit oil-and-gas-bearing sand intervals by statistical-correlation interpretation of GWS data. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 1, рр.54-63. In Rus.